Characterization of Mannanase CtMan26 from Chaetomium thermophilum and Its Application in Mannooligosaccharide Preparation - ZHANG Yiran, GU Xinxi, TAN Suhui, TAN Jianxin, TIAN Hongtao, LU Haiqiang (Shipin Kexue, 2024)
The aim of this study was to achieve efficient expression of mannanase CtMan26 from Chaetomium thermophilum in Pichia pastoris and to investigate the enzymatic properties of CtMan26 and its potential in the preparation of mannooligosaccharides (MOS). The mannanase CtMan26 contained a total of 448 amino acids and consisted of the family 35 carbohydrate-binding module (CBM35), Linker and the catalytic domain module of the GH26 family. Asp-395 and Leu-396 in the catalytic domain and Leu-100 in the auxiliary module of CBM35 were subjected to multiple hydrophobic forces and could form multiple hydrogen bonds with amino acids in the Linker. Recombinant enzyme CtMan26 was expressed with N-glycosylation modification. CtMan26 showed an apparent molecular mass of about 55 kDa. The optimum temperature of the recombinant enzyme was 55 ℃, and the optimum pH was 5.0. The enzymatic activity was maintained at more than 90% of its original value after being incubated at 50 and 60 ℃ for 1 hour, and it showed good stability at pH ranging from 4.0 to 12.0. The specific activity of CtMan26 was 23.15 U/mg, and its Km and Vmax values were 4.75 mg/mL and 27.17 μmol/(min·mg), respectively, when konjac glucomannan was used as the substrate. MOS prepared with the recombinant enzyme mainly consisted of mannose (14.2 mg/L), mannose disaccharides (20.1 mg/L), mannose trisaccharides (6.1 mg/L) and mannose tetrasaccharides (2.5 mg/L). The MOS exhibited good antioxidant capacity, which scavenged (90.80 ± 0.65)% of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, (80.7 ± 1.07)% of 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cation radical, (69.10 ± 1.10)% of hydroxyl radical and (76.7 ± 3.14)% of superoxide anion radical at 2.4 mg/mL concentration. Meanwhile, the MOS had obvious prebiotic properties, which could inhibit the growth of Escherichia coli and promote the growth of the beneficial bacteria Pediococcus pentosaceus and Lactobacillu plantarum the effect being more pronounced with increasing concentration and incubation time. In conclusion, the recombinant mannanase CtMan26 has good enzyme properties and therefore has potential application in the preparation of MOS.